Pulsed radiotherapy to mitigate high tumor burden and generate immune memory - Sezen, Duygu; Barsoumian, Hampartsoum B.; He, Kewen; Hu, Yun; Wang, Qi; Abana, Chike O.; Puebla-Osorio, Nahum; Hsu, Ethan Y.; Wasley, Mark; Masrorpour, Fatemeh; Wang, Jing; Cortez, Maria Angelica; et al. (Frontiers in Immunology, 2022)
Radiation therapy (XRT) has a well-established role in cancer treatment. Given the encouraging results on immunostimulatory effects, radiation has been increasingly used with immune-check-point inhibitors in metastatic disease, especially when immunotherapy fails due to tumor immune evasion. We hypothesized that using high-dose stereotactic radiation in cycles (pulses) would increase T-cell priming and repertoire with each pulse and build immune memory in an incremental manner. To prove this hypothesis, we studied the combination of anti-CTLA-4 and Pulsed radiation therapy in our 344SQ non-small cell lung adenocarcinoma murine model. Primary and secondary tumors were bilaterally implanted in 129Sv/Ev mice. In the Pulsed XRT group, both primary and secondary tumors received 12Gyx2 radiation one week apart, and blood was collected seven days afterwards for TCR repertoire analysis. As for the delayed-Pulse group, primary tumors received 12Gyx2, and after a window of two weeks, the secondary tumors received 12Gyx2. Blood was collected seven days after the second cycle of radiation. The immunotherapy backbone for both groups was anti-CTLA-4 antibody to help with priming. Treatment with Pulsed XRT + anti-CTLA-4 led to significantly improved survival and resulted in a delayed tumor growth, where we observed enhanced antitumor efficacy at primary tumor sites beyond XRT + anti-CTLA-4 treatment group. More importantly, Pulsed XRT treatment led to increased CD4+ effector memory compared to single-cycle XRT. Pulsed XRT demonstrated superior efficacy to XRT in driving antitumor effects that were largely dependent on CD4+ T cells and partially dependent on CD8+ T cells. These results suggest that combinatorial strategies targeting multiple points of tumor immune evasion may lead to a robust and sustained antitumor response.